Recording medium, printing set, and method for manufacturing conductive member

JP2023158367A5Active Publication Date: 2025-04-04GENERAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022068163
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-04-18
Publication Date
2025-04-04
Estimated Expiration
2042-04-18

AI Technical Summary

Technical Problem

Conventional methods for forming conductive layers on substrates, such as IC tags, require multiple steps including resist printing and etching, leading to low productivity and environmental issues, and result in conductive layers with poor conductivity due to the presence of dispersants between metal particles, which also affect heat-sensitive recording layers.

Method used

A recording medium with an ink-receiving layer containing a hydrophilic resin, filler, and water-soluble sulfate is used, allowing inkjet printing of an ink with fine metal particles treated with a dispersant and lower alcohol to form a conductive layer at room temperature without baking, utilizing the sulfate to accelerate drying and enhance conductivity.

Benefits of technology

The method enables rapid formation of a conductive layer with good conductivity, compatible with roll-to-roll operations and preserving heat-sensitive recording capabilities, without equipment corrosion or productivity loss.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

To provide a recording medium which enables formation of a conductive layer having good conductivity by short-time drying, can also sufficiently cope with work by the R to R method, and does not affect devices performing work by the method, a printing set including the recording medium and ink for inkjet printing, and a manufacturing method for manufacturing a conductive member such as an IC tag using the printing set with good productivity.SOLUTION: A recording medium includes an ink receptive layer which is formed on at least one surface of a base material and constitutes a printed surface, contains a hydrophilic resin, a filler and a water-soluble sulphate, and receives ink containing metal fine particles treated with a dispersant, water and lower alcohol. A printing set includes the recording medium and ink. A method for manufacturing a conductive member includes a step of inkjet printing the ink on a printed surface of the recording medium, and forming a conductive layer.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a recording medium including a printing surface for forming a conductive layer by inkjet printing an ink containing metal fine particles, a printing set including the recording medium and an ink for inkjet printing, and a manufacturing method for manufacturing a conductive member using such a printing set.

Background Art

[0002] In recent years, IC tags such as RFID have been widely used for product management and the like. Conventional IC tags are generally composed of an antenna made of a metal foil such as an aluminum foil laminated on the surface of a sheet-like substrate, and an IC chip mounted on the antenna.

Prior Art Documents

Patent Documents

[0003]

Patent Document 1

Summary of the Invention

Problems to be Solved by the Invention

[0004] However, in the above prior art, in order to form a pattern of the laminated metal foil into a predetermined antenna shape, a large number of processes such as resist printing, etching treatment, and resist removal are required, and there is a problem that productivity is low. Also, the treatment of waste liquid generated during etching treatment and resist removal becomes a problem. Therefore, it has been considered to form a conductive layer directly on the surface of a substrate into a predetermined planar shape by inkjet printing using an ink made from a metal colloid solution in which metal fine particles (metal nanoparticles) are dispersed in a dispersion medium such as water.

[0005] Metal colloidal solutions are produced, for example, by adding a dispersant such as a polymer dispersant and a reducing agent to an aqueous solution of a metal salt, or by adding dextrin, which acts as both a dispersant and a reducing agent, to reduce and precipitate the metal into fine particles in the solution. These particles are then subjected to processes such as desalting and concentration. The precipitated metal particles are then treated on the surface with a dispersant, i.e., covered with a dispersant, to maintain their dispersion stability in the metal colloidal solution.

[0006] Ink is prepared by adding a dispersion medium such as water or a water-soluble organic solvent, or a surfactant, to a metal colloidal solution as needed. However, the layer formed by inkjet printing using such ink does not have good conductivity because the dispersant is interposed between the metal nanoparticles; it is merely a precursor layer to a conductive layer.

[0007] In order to achieve good conductivity in the precursor layer and for it to function fully as a conductive layer, the formed precursor layer must be fired to remove the dispersant interposed between the metal nanoparticles. Therefore, this formation method cannot be used to form a conductive layer on a substrate such as a heat-sensitive plastic.

[0008] Furthermore, in IC tags and the like, it has been considered to form a thermal recording layer on the surface of the substrate opposite to the surface where the antenna is formed, so that the opposite surface can be used as a thermal recording surface for recording visible information such as barcodes. However, in the above-mentioned formation method which involves firing, the thermal recording surface changes color when fired, and the thermal recording function is lost. Therefore, it is not possible to manufacture IC tags and the like that contain a conductive layer that has conductivity suitable for an antenna and also possess thermal recording functionality.

[0009] Patent Document 1 discloses a method for forming a conductive layer on the surface (printing surface) of a recording medium having a porous ink-receiving layer containing a halogen salt formed on a sheet-like substrate, without firing, in an environment of room temperature (5-35°C).

[0010] In other words, when an ink made from a metal colloidal solution is supplied to the printing surface of the ink-receiving layer, the water in the ink penetrates into the ink-receiving layer and dissolves the halogen salts contained in the ink-receiving layer. Then, the dispersant coating the surface of the metal nanoparticles reacts with the halogen ions produced by the dissolution and detaches from the surface of the metal nanoparticles, and the metal nanoparticles remain on the printing surface while being incorporated into the ink-receiving layer along with the water.

[0011] Therefore, on the printed surface, the drying of the ink is accelerated, and the numerous metal microparticles remaining on the printed surface aggregate as the dispersant is removed and the opportunity for them to come into direct contact with each other increases. As a result, a conductive layer with appropriate conductivity is formed at room temperature without the need for firing. In other words, the halogen salt contained in the ink receiving layer functions as a conductivity-generating agent that replaces the firing process. This recording medium can be considered for application to the formation of conductive layers by inkjet printing.

[0012] However, when a volatile lower alcohol with 5 or fewer carbon atoms is used in combination with water as a dispersion medium for the ink, particularly to improve the drying properties of the ink and shorten the drying time, the recording medium described in Patent Document 1 tends to actually decrease the drying properties of the ink. Furthermore, it takes a relatively long time to form a conductive layer with appropriate conductivity, resulting in cases where, for example, the recording medium after inkjet printing must be left to dry for a certain period of time.

[0013] Therefore, the above-mentioned recording media have the problem of not being able to adequately handle roll-to-roll (RtoR) operations, which are particularly important for productivity in industrial applications. RtoR operations generally refer to the process of continuously winding a recording medium, which is wound into a long roll, into a roll while unwinding it from the roll and performing some kind of processing, in this case, the formation of a conductive layer by inkjet printing.

[0014] Furthermore, because halogen salts are highly corrosive to metals, they may render metal components such as metal rolls, which are typically incorporated into equipment used in roll-to-roll (RtoR) operations, unusable.

[0015] The object of the present invention is to provide a recording medium that can form a conductive layer with good conductivity by drying in a shorter time than currently possible, is fully compatible with RtoR (return to return) methods, and does not affect the equipment used for such work; a printing set including the recording medium and ink for inkjet printing; and a manufacturing method for producing conductive members such as IC tags with high productivity using the printing set. [Means for solving the problem]

[0016] The present invention relates to a recording medium comprising a printing surface for inkjet printing an ink containing metal fine particles treated with a dispersant, water, and a lower alcohol to form a conductive layer, • Substrate and - An ink receiving layer formed on at least one side of the substrate and constituting the printing surface, comprising a hydrophilic resin, a filler, and a sulfate capable of forming a hydrate, which receives the ink, This recording medium is characterized by containing [a specific element].

[0017] Furthermore, the present invention, The recording medium of the present invention, • An ink comprising metal fine particles treated with a dispersant, water, and a lower alcohol, which is inkjet printed onto the printing surface of the recording medium to form the conductive layer, This is a print set that includes [something].

[0018] Furthermore, the present invention is a method for manufacturing a conductive member, comprising the step of inkjet printing an ink containing metal fine particles treated with a dispersant, water, and a lower alcohol onto the printing surface of the recording medium of the present invention to form the conductive layer. [Effects of the Invention]

[0019] According to the present invention, a conductive layer having good conductivity can be formed by drying in a shorter time than the current situation. Therefore, it can sufficiently cope with the work in the RtoR method and does not affect the apparatus or the like for performing the work. A recording medium, a printing set including the recording medium and ink for inkjet printing, and a manufacturing method for productively manufacturing a conductive member such as an IC tag can be provided using such a printing set.

Embodiments for Carrying Out the Invention

[0020] 《Recording Medium》 As described above, the present invention is a recording medium including a printing surface for forming a conductive layer by inkjet printing an ink containing metal fine particles, water, and a lower alcohol treated with a dispersant, · a base material, · formed on at least one surface of the base material, including a hydrophilic resin, a filler, and a sulfate capable of forming a hydrate as a conductivity developer, constituting a printing surface for forming a conductive layer by inkjet printing, and an ink receiving layer for receiving ink, characterized by including the above.

[0021] When inkjet printing is performed on the printing surface of the above-described conventional recording medium using an ink containing a mixed dispersion medium of water and a lower alcohol, the drying property of the ink is rather deteriorated. The main cause is the salt of halogen used as a conductivity developer in the conventional recording medium. That is, since the salt of halogen has low solubility in the above mixed dispersion medium, combined with the use of a lower alcohol, the concentration of water in the ink becomes low, and water cannot be effectively taken into the ink receiving layer, and the ink cannot be quickly dried.

[0022] Therefore, in the conventional recording medium, the drying property of the ink containing the above mixed dispersion medium is rather deteriorated, and the ink cannot be sufficiently dried in a short time suitable for the work in the RtoR method as described above.

[0023] In contrast, according to the recording medium of the present invention, a sulfate that can form a hydrate, that is, a basically water-soluble sulfate, contained in the ink-receiving layer, functions as a conductivity imparting agent, similar to conventional halogen salts. Specifically, the water-soluble sulfate dissolves in the water in the ink to generate sulfate ions, and these generated sulfate ions react with a dispersant coating the surface of the metal nanoparticles, thereby causing the dispersant to detach from the surface of the metal nanoparticles and be incorporated into the ink-receiving layer along with the water.

[0024] Therefore, the drying of the ink on the printed surface is accelerated, and the numerous metal microparticles remaining on the printed surface aggregate as the dispersant is removed and the opportunity for them to come into direct contact with each other increases as the ink dries. As a result, a conductive layer with appropriate conductivity is formed at room temperature without the need for firing.

[0025] Furthermore, since water-soluble sulfates have particularly superior solubility in mixed dispersion media of water and lower alcohols compared to conventional halogen salts, water can be more effectively incorporated into the ink-receiving layer through the mechanism described above. Therefore, by combining this with an ink containing the above-mentioned mixed dispersion medium, which inherently has high drying properties, the ink can be dried more quickly in a shorter time, forming a conductive layer with appropriate conductivity.

[0026] Furthermore, since water-soluble sulfates do not exhibit strong corrosive properties towards metals like halogen salts, the present invention makes it possible to provide a recording medium that can adequately handle RtoR (reverse-to-reverse) operations without affecting the equipment used for such operations.

[0027] <Base material> Examples of substrates constituting the recording medium of the present invention include paper and resin films, of which examples of paper include high-quality paper, medium-quality paper, art paper, bonded paper, recycled paper, paralyta paper, cast-coated paper, corrugated cardboard, condenser paper, and glassine paper.

[0028] Examples of resins that make up the resin film include polyolefin resins such as polyethylene and polypropylene; vinyl chloride resins such as polyvinyl chloride, vinyl chloride copolymer, and polyvinylidene chloride; polyester resins such as polyethylene terephthalate and polyethylene naphthalate; styrene resins such as polystyrene and ABS resin; acrylic resins such as polymethyl methacrylate; polyamide, polyimide, polycarbonate, triacetate, epoxy resin, polyarylate, polysulfone, polyethersulfone, fluororesin, phenoxy resin, polyphenylene sulfide, cellophane, and nylon. One or more of these resins can be used.

[0029] In particular, as explained above, according to the present invention, since firing is not required when forming the conductive layer, it is possible to use a plastic film with low heat resistance, such as the polypropylene mentioned above, as the base material. Alternatively, a laminate made by laminating two or more of the above-mentioned papers or resin films can also be used as the base material.

[0030] The recording medium of the present invention is configured such that an ink-receiving layer coating is applied to one or both sides of the above-mentioned substrate, and the coating is dried to form an ink-receiving layer, thereby making one or both sides a printable surface for forming a conductive layer by inkjet printing.

[0031] The thickness of the substrate can be arbitrarily set depending on the application of the recording medium or conductive material being manufactured, or the type and configuration of the substrate used (single layer or laminate, single-sided or double-sided printing surface), etc.

[0032] Furthermore, since firing is not required when forming the conductive layer, the recording medium of the present invention can also be configured such that one side of the substrate has an ink-receiving layer formed on it to serve as the printing surface, while the opposite side has a thermal recording layer formed on it as described above, thereby functioning as a thermal recording surface.

[0033] (Thermal recording layer) The thermal recording layer constituting the thermal recording surface can be constructed, as in the past, by combining, for example, a basic and normally colorless dye (leuco dye) with an acidic color developer. The thickness of the thermal recording layer can be set arbitrarily. However, considering the improvement of the thermal responsiveness of the thermal recording layer and the clarity of the print, the thickness of the thermal recording layer is preferably 4 μm or more, particularly 6 μm or more, and preferably 10 μm or less, particularly 8 μm or less.

[0034] (Barrier layer) In particular, when the substrate is a permeable paper, it is preferable to interpose a barrier layer between the substrate and the ink-receiving layer. The barrier layer is preferably a layer that can physically and chemically isolate the two in order to suppress the penetration of the coating for the ink-receiving layer or components contained in the ink that is inkjet printed on the printed surface, which is the surface of the ink-receiving layer, through the substrate into the thermal recording layer.

[0035] By interposing such a barrier layer, it is possible to suppress the reaction of the leuco dye in the thermal recording layer with components contained in the coating agent and ink for the ink receiving layer, particularly alcohol, which can cause the entire thermal recording layer to develop its base color. Furthermore, it is possible to suppress poor color development during thermal recording by hindering the reaction between the color developer and the leuco dye.

[0036] Furthermore, the barrier layer also functions to prevent the substrate, especially paper-based materials, from becoming soggy and warped due to moisture and alcohol in the ink used for inkjet printing on the printed surface. In addition, the barrier layer also functions as a so-called sealant, preventing the substrate, especially paper-based materials, from becoming soggy and warped when a water-based ink-receiving coating is applied to the substrate.

[0037] The barrier layer can be formed from various materials having these functions, particularly resins. Examples of resins that form the base of the barrier layer include polyvinyl alcohol-based resins having any degree of saponification, such as fully saponified polyvinyl alcohol and partially saponified polyvinyl alcohol; modified polyvinyl alcohol-based resins such as acetoacetyl-modified polyvinyl alcohol, diacetone-modified polyvinyl alcohol, carboxyl-modified polyvinyl alcohol, silicon-modified polyvinyl alcohol, and itaconic acid-modified polyvinyl alcohol; ethylene-vinyl alcohol copolymers, urethane resins, and butenediol-vinyl alcohol copolymers having any degree of saponification. One or more of these resins can be used.

[0038] The thickness of the barrier layer can be set arbitrarily. However, considering the need to make the barrier layer function as described above more effective, the thickness of the barrier layer is preferably 1 μm or more, more preferably 2 μm or more, and more preferably 6 μm or less, and more preferably 4 μm or less.

[0039] <Ink-receiving layer> The ink-receiving layer formed on one or both sides of the substrate contains a hydrophilic resin, a filler, and a water-soluble sulfate, as described above. The ink-receiving layer is formed by applying a coating containing these components to one or both sides of the substrate and then drying it, as explained earlier.

[0040] The thickness of the ink-receiving layer can be arbitrarily set depending on the application of the recording medium or conductive material being manufactured, or the type and configuration of the substrate used (whether the printing surface is single-sided or double-sided). However, the thickness of the ink-receiving layer is preferably 1 μm or more, more preferably 3 μm or more, and especially preferably 5 μm or more, and 40 μm or less, more preferably 35 μm or less, and especially preferably 30 μm or less.

[0041] If the thickness of the ink receiving layer is less than this range, the effect of efficiently incorporating the mixing dispersion medium and metal particle dispersant in the ink into the ink receiving layer and rapidly drying the ink may be insufficient. On the other hand, if the thickness of the ink receiving layer exceeds the above range, depending on the type and thickness of the substrate, the conformability of the ink receiving layer to the substrate may decrease, making it more prone to peeling off the substrate. In contrast, by setting the thickness of the ink receiving layer within the above range, it is possible to impart appropriate flexibility to the ink receiving layer, further improving the effect of rapidly drying the ink while maintaining a state that is less likely to peel off the substrate.

[0042] (hydrophilic resin) The hydrophilic resin functions as a binder to form an ink-receiving layer by binding fillers and sulfates. Furthermore, when ink is inkjet printed onto the printed surface (the surface of the ink-receiving layer), the hydrophilic resin incorporates the mixed dispersion medium of water and lower alcohols from the ink into the ink-receiving layer, accelerating ink drying. Additionally, the hydrophilic resin dissolves sulfates with the incorporated water, generating sulfate ions. These sulfate ions react with the dispersant coating the surface of the metal microparticles, causing them to detach from the surface and be incorporated into the ink-receiving layer along with the water.

[0043] As hydrophilic resins, various conventionally known hydrophilic resins can be used, such as polyvinyl acetal resins like polyvinyl butyral; acrylic resins like polyacrylic acid; polyvinyl alcohol resins; urethane resins; starch resins; and carboxymethylcellulose resins.

[0044] However, the polyvinyl alcohol whose effectiveness was verified in the examples of Patent Document 1 has some swelling properties when mixed and dispersed with water and lower alcohol, which may affect drying properties. Polyvinyl acetals obtained by acetalizing polyvinyl alcohol, especially those with a degree of acetalization exceeding 50 mol%, show a similar tendency.

[0045] In contrast, polyvinyl acetal, which is obtained by acetalizing polyvinyl alcohol and has a degree of acetalization of 50 mol% or less, has excellent absorption of a mixed dispersion medium of water and lower alcohol, does not swell in such a mixed dispersion medium, and also has excellent drying properties. For this reason, polyvinyl acetal with a degree of acetalization of 50 mol% or less is preferably used as a hydrophilic resin.

[0046] Specific examples of polyvinyl acetals with an acetalization degree within the above range include, but are not limited to, the S-LEC® series of polyvinyl acetals manufactured by Sekisui Chemical Co., Ltd., such as KX-1 [acetalization degree: 8±2 mol%, solid content: 8±2 mass%], KX-5 [acetalization degree: 9±2 mol%, solid content: 8±2 mass%], KW-M [acetalization degree: 24±3 mol%, solid content: 20±2 mass%], and KW-10 [acetalization degree: 9±2 mol%, solid content: 24±2 mass%], which are supplied as aqueous solutions. One or more of these polyvinyl acetals can be used.

[0047] However, this invention does not exclude polyvinyl alcohol or polyvinyl acetal with a degree of acetalization exceeding 50 mol%, and these resins can also be used as hydrophilic resins.

[0048] Specific examples of polyvinyl alcohol include, but are not limited to, the Kuraray Poval® series of polyvinyl alcohols manufactured by Kuraray Co., Ltd., all of which are supplied as solids with a volatile content of 5% or less for use as binders. Examples include fully saponified polyvinyl alcohols such as PVA-105, PVA-117, and PVA-124, partially saponified polyvinyl alcohols such as PVA-205, PVA-217, and PVA-224, and partially saponified high-purity polyvinyl alcohols such as PVA-205C, PVA-217C, and PVA-224C. One or more of these polyvinyl alcohols can be used.

[0049] Furthermore, specific examples of polyvinyl acetals with an acetalization degree exceeding 50 mol% include, but are not limited to, BL-10 (acetalization degree: approximately 70 mol%), BL-1 (acetalization degree: approximately 63 mol%), BL-1H (acetalization degree: approximately 69 mol%), BL-S (acetalization degree: approximately 72 mol%), BL-2H (acetalization degree: approximately 69 mol%), BL-5Z (acetalization degree: approximately 77 mol%), and BL-7Z (acetalization degree: approximately 69 mol%) from Sekisui Chemical Co., Ltd., all of which are supplied as solids with a volatile content of 3% or less. One or more of these polyvinyl acetals can be used.

[0050] The proportion of hydrophilic resin is preferably 5 parts by mass or more, particularly 10 parts by mass or more, and preferably 35 parts by mass or less, particularly 30 parts by mass or less, based on solid content, out of 100 parts by mass of the total amount of solids forming the ink receiving layer. If the proportion of hydrophilic resin is below this range, the flexibility and conformability of the ink receiving layer to the substrate may decrease, making it more prone to peeling off from the substrate.

[0051] On the other hand, if the proportion of hydrophilic resin exceeds the above range, the proportion of filler will be relatively low, and therefore, the effect of making the ink-receiving layer porous and improving the absorption of the mixed dispersion medium contained in the ink, as explained in the next section, may not be sufficiently obtained. Also, the proportion of sulfate will be relatively low, and the effect of incorporating sulfate, which allows the ink to dry more quickly and forms a conductive layer with appropriate conductivity, may not be obtained.

[0052] In contrast, by setting the proportion of hydrophilic resin within the above range, it is possible to impart appropriate flexibility to the ink-receiving layer, maintaining a state that is difficult to peel off from the substrate, while making the ink-receiving layer porous and improving the absorption of the mixed dispersion medium contained in the ink. Furthermore, it becomes possible to dry the ink more quickly in a shorter time and form a conductive layer with appropriate conductivity.

[0053] (filling material) The filler functions to improve the absorption of the mixed dispersion medium contained in the ink by making the ink-receiving layer porous through dispersion in the hydrophilic resin. Various fillers, either inorganic or organic, can be used as the filler.

[0054] Examples of inorganic fillers include porous or non-porous fine particles made of light calcium carbonate, heavy calcium carbonate, magnesium carbonate, kaolin, talc, calcium sulfate, barium sulfate, titanium dioxide, zirconia, cerium, antimony oxide, zinc oxide, zinc sulfide, zinc carbonate, satin white, aluminum silicate, diatomaceous earth, calcium silicate, magnesium silicate, silica (amorphous synthetic silica, colloidal silica, silica sol, etc.), alumina, colloidal alumina, alumina hydrate, lithopone, zeolite, hydrated halloysite, magnesium hydroxide, etc.

[0055] Examples of organic fillers include porous or non-porous fine particles made from polyethylene resins, polystyrene resins, (meth)acrylic resins, vinyl chloride resins, vinyl acetate resins, polyester resins, styrene / acrylic resins, styrene / butadiene resins, styrene / isoprene resins, methyl methacrylate / butyl methacrylate resins, polycarbonate resins, polyacrylate resins, silicone resins, urea resins, melamine resins, epoxy resins, phenolic resins, diallyl phthalate resins, and the like.

[0056] The average particle size of the filler can be appropriately selected depending on the type of filler (inorganic or organic, porous or non-porous), etc. However, as a filler, various types of silica (colloidal silica, silica sol, etc.) that are acidic, neutral, or alkaline and have a primary particle size of about 1 nm to 100 nm are preferred in terms of their effect on improving the absorbency of the mixed dispersion medium.

[0057] The proportion of the filler can also be appropriately selected depending on the type of filler. For example, if the filler is silica, the proportion of silica is preferably 40 parts by mass or more, particularly 50 parts by mass or more, and preferably 80 parts by mass or less, and particularly 70 parts by mass or less, out of 100 parts by mass of the total amount of solids forming the ink receiving layer. Furthermore, the proportion of silica is preferably 200 parts by mass or more, particularly 250 parts by mass or more, and preferably 400 parts by mass or less, and particularly 350 parts by mass or less, per 100 parts by mass of hydrophilic resin.

[0058] If the silica content is below this range, the effect of making the ink-receiving layer porous and improving the absorbency of the mixed dispersion medium contained in the ink may not be sufficiently obtained. On the other hand, if the silica content exceeds the above range, the proportion of hydrophilic resin as a binder will be relatively low, which may reduce the flexibility and conformability of the ink-receiving layer to the substrate, making it more prone to peeling off the substrate.

[0059] In contrast, by setting the silica content within the above range, the ink receiving layer can be given appropriate flexibility, maintaining a state where it is difficult to peel off from the substrate, while the ink receiving layer can be made porous, thereby improving the absorption capacity of the mixed dispersion medium contained in the ink.

[0060] When using colloidal silica or silica sol, which are silica nanoparticles dispersed in any dispersion medium, the above ratio refers to the parts by mass of the silica itself as solid content contained in the colloidal silica or the like.

[0061] One of these fillers, or two or more of them with different types or particle sizes, can be used.

[0062] (Sulfate) Various sulfates that can form hydrates, i.e., are water-soluble, can be used as sulfates. Examples of water-soluble sulfates include sodium sulfate, aluminum sulfate, and magnesium sulfate. Among these, at least one selected from the group consisting of sodium sulfate and aluminum sulfate is particularly preferred in terms of the effects of incorporating the aforementioned sulfates.

[0063] Of these, sodium sulfate can be either anhydrous or decahydrate, depending on the crystallization temperature. Aluminum sulfate can be either 18-hydrate, synthesized by concentrating and cooling a solution of aluminum hydroxide dissolved in sulfuric acid, or 16-hydrate, decahydrate, hexahydrate, or anhydrous, obtained by heat-treating the 18-hydrate. Furthermore, magnesium sulfate can be either naturally occurring heptahydrate, or monohydrate or anhydrous, obtained by heat-treating the heptahydrate.

[0064] The proportion of sulfate is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, and 35 parts by mass or less, and particularly preferably 30 parts by mass or less, based on anhydrous basis, of 100 parts by mass of the total amount of solids forming the ink receiving layer. Furthermore, the proportion of sulfate is preferably 25 parts by mass or more, more preferably 50 parts by mass or more, and 175 parts by mass or less, and particularly preferably 150 parts by mass or less, based on anhydrous basis, of 100 parts by mass of hydrophilic resin.

[0065] If the sulfate ratio is below this range, the effect of incorporating sulfates—rapidly drying the ink in a shorter time and forming a conductive layer with appropriate conductivity—may not be achieved. On the other hand, if the sulfate ratio exceeds the above range, the excess sulfate may act as an inhibitor, potentially reducing the conductivity of the conductive layer. Conversely, by setting the sulfate ratio within the above range, it becomes possible to rapidly dry the ink in a shorter time and form a conductive layer with appropriate conductivity.

[0066] Printing Set As described above, the printing set of the present invention includes the recording medium of the present invention and an ink for forming a conductive layer on the printing surface of the recording medium.

[0067] <ink> The inks that make up the printing set are prepared, as in the conventional method, using a metal colloid solution as a raw material, in which metal nanoparticles are dispersed in a dispersion medium such as water. Examples of metals that form the metal nanoparticles include gold, silver, copper, platinum, palladium, rhodium, ruthenium, iridium, osmium, nickel, bismuth, aluminum, zinc, tin, cobalt, and iron. One of these metals or an alloy of two or more metals can be used. In particular, silver or an alloy thereof is preferred for use as the antenna of the IC chip in the aforementioned IC tag.

[0068] Metal colloidal solutions containing metal nanoparticles are produced by a process that reduces and precipitates the metal into fine particles in a liquid, similar to conventional methods. This is done by adding a dispersant such as a polymer dispersant and a reducing agent to an aqueous solution of a metal salt, or by adding dextrin, which acts as both a dispersant and a reducing agent. The precipitated metal nanoparticles are then treated on the surface with a dispersant, i.e., covered with a dispersant, to maintain dispersion stability in the metal colloidal solution. Alternatively, metal colloidal solutions can also be produced by dispersing metal nanoparticles, manufactured by various methods such as gas-phase or liquid-phase methods, together with a dispersant in a dispersion medium such as water.

[0069] The ink constituting the printing set of the present invention is prepared by adding water and a lower alcohol as a dispersion medium to the above-mentioned metal colloid solution, and further adding a higher alcohol or surfactant as necessary. By using a mixed dispersion medium of water and a volatile lower alcohol as the dispersion medium, in combination with the use of the recording medium of the present invention described above, the drying properties of the ink can be improved, and the drying time can be further shortened.

[0070] Various lower alcohols with 5 or fewer carbon atoms can be used, and lower alcohols with 1 to 3 carbon atoms are particularly preferred due to their higher volatility. Examples of lower alcohols with 1 to 3 carbon atoms include methanol, ethanol, 1-propanol, and 2-propanol. One or more of these lower alcohols can be used.

[0071] The ratio of water to lower alcohol in a mixed dispersion medium can be set arbitrarily. However, the proportion of water in the total amount of water and lower alcohol having 1 to 3 carbon atoms is preferably 20% by mass or more, particularly 30% by mass or more, and preferably 75% by mass or less, particularly 70% by mass or less. If the proportion of water is below this range, the proportion of lower alcohol having 1 to 3 carbon atoms becomes relatively too high, reducing the solubility of sulfates contained in the ink receiving layer of the recording medium. As a result, the effect of incorporating the dispersant covering the surface of metal nanoparticles into the ink receiving layer and imparting appropriate conductivity to the conductive layer, as explained above, may become insufficient.

[0072] Furthermore, because the ink dries out easily, when this ink is used, especially in on-demand inkjet printers, and printing is resumed after the decapping time, the nozzles may become clogged, causing streaking and other issues, and intermittent printing performance may be compromised. Decapping time refers to the time during intermittent printing when ink in nozzles that are in a standby state where ink droplets are not ejected according to the printing pattern is exposed to the outside air.

[0073] On-demand inkjet printers typically have a function to close (cap) the nozzles when the printer is stopped, to prevent the ink inside the nozzles from drying out and clogging due to continued exposure to the outside air. However, the caps are released during printing. Therefore, nozzles that are in standby mode, especially during intermittent printing, remain open (decapped) until the next ink droplet is ejected, and during that time, the ink inside the nozzles is continuously exposed to the outside air.

[0074] Therefore, the longer the above-mentioned time, i.e., the decapping time, the more likely the ink is to dry out and clog the nozzles. The ability to resist drying and nozzle clogging during the decapping time is evaluated as a measure of "intermittent printability." The longer the decapping time without clogging, the better the intermittent printability of the ink can be considered.

[0075] On the other hand, if the proportion of water in the mixed solvent exceeds the aforementioned range, the proportion of lower alcohols with 1 to 3 carbon atoms decreases relatively, and the effect of using these lower alcohols in combination with water to improve ink drying properties and shorten drying time may become insufficient. In contrast, by setting the proportion of water within the aforementioned range, it becomes possible to provide an ink that has excellent intermittent printing properties, improves drying properties, and can form a conductive layer with appropriate conductivity in a shorter time. Note that the proportion of water in the mixed solvent is the total ratio of water added during ink preparation and water contained in the metal colloid solution.

[0076] As mentioned above, higher alcohols may be added to the ink. During the decapping time described above, the higher alcohols form a thin film that covers the ink surface at the tip of the nozzle, thereby preventing the nozzle from clogging due to the drying of the ink. In other words, higher alcohols dissolve well in lower alcohols with 1 to 3 carbon atoms, but are hardly soluble in water.

[0077] However, at the tip of the nozzle, near the ink surface, i.e., the interface with air, the lower alcohol evaporates quickly, leaving behind water that does not evaporate easily, and the concentration of this water tends to increase. As a result, higher alcohols are more likely to precipitate from the ink, and the precipitated higher alcohols form a thin film covering the ink surface, suppressing the drying of the ink. Therefore, by adding higher alcohols, nozzle clogging can be further suppressed, and the intermittent printing properties of the ink can be further improved. As the higher alcohol, higher alcohols with 12 or more carbon atoms are particularly preferred. There is no particular upper limit to the number of carbon atoms of the higher alcohol, but it is preferable that it be 18 or less.

[0078] While not limited to these, examples of higher alcohols with 12 or more carbon atoms include the following from the Conol® series manufactured by Shin Nippon Rika Co., Ltd.: 1275 [lauryl alcohol, C12: 70-80%, C14: 20-30%], 1495 [myristyl alcohol, C14: ≥99%], 1695 [cetyl alcohol, C16: ≥99%], 30OC [cetostearyl alcohol, C16: 68-78%, C18: 22-32%], and 30RC [cetostearyl Examples include alcohols with C16: 65-75%, C18: 25-35%, 30CK (cetostearyl alcohol, C16: 45-55%, C18: 45-55%), 1865 (stearyl alcohol, C16: 25-35%, C18: 65-75%), 30F (stearyl alcohol, C16: 7-17%, C18: 83-93%), 30S (stearyl alcohol, C16: ≤5%, C18: ≥95%), 30SS (stearyl alcohol, C18: ≥99%), etc. One or more of these higher alcohols can be used.

[0079] Surfactants function to adjust the wettability of ink to inkjet printer nozzles and other components, thereby optimizing the ejection of ink droplets from those nozzles. Anionic surfactants, cationic surfactants, amphoteric surfactants, and nonionic surfactants can all be used.

[0080] Of the components that make up the ink, the proportion of metal fine particles is preferably 5% by mass or more, particularly 10% by mass or more, and preferably 40% by mass or less, particularly 30% by mass or less, of the total amount of ink. The proportion of metal fine particles can be appropriately adjusted within the above range depending on the conductivity of the conductive layer to be formed. In the case of an IC chip antenna, where particularly high conductivity is required, the proportion of metal fine particles should be set to a higher range within the above range. However, even if the conductivity is low after one print, it is possible to improve the conductivity by printing two or three times in layers.

[0081] The proportion of higher alcohols with 12 or more carbon atoms is preferably 0.1% by mass or more, and preferably 1.0% by mass or less, of the total amount of ink. The proportion of surfactants is preferably 0.1% by mass or more, and preferably 0.5% by mass or less, of the total amount of ink.

[0082] If the proportion of higher alcohols is below the above range, the aforementioned effect of improving the intermittent printability of the ink by incorporating these higher alcohols may not be sufficiently obtained. On the other hand, if the proportion of higher alcohols exceeds the above range, the stability of the ink may decrease, or higher alcohols may remain in the conductive layer formed on the printed surface, reducing the conductivity of the conductive layer. In contrast, by setting the proportion of higher alcohols within the above range, it is possible to further improve the intermittent printability of the ink while suppressing the decrease in the conductivity of the conductive layer.

[0083] The ratio of water to the total amount of lower alcohols with 1 to 3 carbon atoms represents the remaining amount of other components. In other words, when the ratios of metal particles, dispersants, added higher alcohols, and surfactants contained in the metal colloid solution are set within the above ranges, the blending amounts should be set so that the total amount of ink is 100% by mass.

[0084] Method for manufacturing conductive materials The method for manufacturing a conductive member of the present invention is characterized by using the printing set of the present invention described above. That is, the manufacturing method of the present invention includes a step of forming a conductive layer pattern on the printed surface, which is the surface of the ink-receiving layer formed on one or both sides of the recording medium of the present invention, by inkjet printing using the ink of the printing set.

[0085] According to the manufacturing method of the present invention, the ink can be sufficiently dried in a short time suitable for RtoR (return to return) processing, without firing, in an environment at room temperature, and to form a conductive layer with appropriate conductivity, thereby manufacturing any conductive member. For example, it becomes possible to manufacture a conductive member using a plastic film with low heat resistance, such as polypropylene, as the base material.

[0086] Furthermore, an IC tag can be manufactured by forming an ink-receiving layer on one side of the substrate to serve as the printing surface, and forming a thermal recording layer on the opposite side, as described above, to function as a thermal recording surface. In other words, an IC tag is manufactured by first forming a conductive layer as an antenna on the printing surface using inkjet printing with the ink from the printing set, then mounting an IC chip on the conductive layer using any method, and finally recording visible information such as a barcode on the thermal recording surface on the opposite side using thermal recording. [Examples]

[0087] The present invention will be further described below based on examples and comparative examples, but the configuration of the present invention is not limited to these examples.

[0088] Recording media <Example i> (Preparation of coating material for ink receiving layer) The following components were blended in the proportions shown in Table 1, and then a mixed dispersion medium of water and ethanol was added and stirred to prepare a coating agent for the ink receiving layer.

[0089] Hydrophilic resin: Polyvinyl acetal [S-Rec KX-1 manufactured by Sekisui Chemical Co., Ltd., degree of acetalization: 8±2 mol%, solid content: 8±2 mass%] Filler: Colloidal silica [Quattron® PL-3 manufactured by Fuso Chemical Industries, Ltd., primary particle size: 35 nm, silica concentration: 20%] Sulfates: Sodium sulfate anhydrous In the table, the part by mass of the hydrophilic resin refers to the part by mass of polyvinyl acetal itself as a solid component contained in KX-1, which is supplied as a solution of isopropanol and water, and the part by mass of silica as a filler refers to the part by mass of silica itself as a solid component contained in colloidal silica PL-3.

[0090] [Table 1]

[0091] (Formation of the substrate and barrier layer) The base material has a basis weight of 64.0 g / m². 2 High-quality paper was prepared, and a barrier coating agent containing a urethane resin was applied to one side of the substrate and then dried to form a barrier layer with a thickness of 3 μm.

[0092] (Creation of recording media) The previously prepared ink-receiving layer coating was applied to the barrier layer of the above-mentioned substrate and then dried to form an ink-receiving layer with a thickness of 10 μm, thereby creating a recording medium.

[0093] <Example ii> An ink-receiving layer coating was prepared in the same manner as in Example i, except that an equal amount of anhydrous aluminum sulfate was added as the sulfate, and a recording medium was manufactured.

[0094] <Example iii> An ink-receiving layer coating was prepared in the same manner as in Example i, except that an equal amount of anhydrous magnesium sulfate was added as the sulfate, and a recording medium was manufactured.

[0095] <Comparative example i> An ink-receiving layer coating was prepared in the same manner as in Example i, except that the same amount of sodium chloride, a halogen salt, was added instead of sulfate, and a recording medium was fabricated.

[0096] <Example iv> An ink-receiving layer coating was prepared in the same manner as in Example i, except that the same amount of polyvinyl alcohol [Kuraray Poval PVA-117, solid, manufactured by Kuraray Co., Ltd.] was added as a hydrophilic resin, and a recording medium was made.

[0097] <Example v> An ink-receiving layer coating was prepared in the same manner as in Example i, except that polyvinyl acetal [S-Rec KW-M manufactured by Sekisui Chemical Co., Ltd., degree of acetalization: 24±3 mol%, solid content: 20±2 mass%] was blended as a hydrophilic resin so that the solid content was the same. A recording medium was then made.

[0098] <Example vi> An ink-receiving layer coating was prepared in the same manner as in Example i, except that the same amount of polyvinyl acetal [S-Rec BL-1 manufactured by Sekisui Chemical Co., Ltd., degree of acetalization: approximately 63 mol%, solid] was added as a hydrophilic resin, and a recording medium was made.

[0099] <Examples vii-xii> An ink-receiving layer coating was prepared in the same manner as in Example i, except that polyvinyl acetal as a hydrophilic resin [S-Rec KX-1 manufactured by Sekisui Chemical Co., Ltd., degree of acetalization: 8±2 mol%, solid content: 8±2 mass%], colloidal silica as a filler [Quattron PL-3 manufactured by Fuso Chemical Industries, Ltd., primary particle size: 35 nm, silica concentration: 20%], and sulfate were blended in the parts by mass shown in Table 2, and a recording medium was made.

[0100] In the table, the part by mass of the hydrophilic resin refers to the part by mass of polyvinyl acetal itself as a solid component contained in KX-1, which is supplied as a solution of isopropanol and water, and the part by mass of silica as a filler refers to the part by mass of silica itself as a solid component contained in colloidal silica PL-3.

[0101] [Table 2]

[0102] "ink" <Ink 1> (Preparation of silver colloid solution) To a nitric acidic silver nitrate aqueous solution containing 16.98 parts by mass of silver nitrate, 74.90 parts by mass of water, and 2 parts by mass of 0.1 N nitric acid, 0.52 parts by mass of a polymeric dispersant [Disperbyk (registered trademark) 190, manufactured by Bic Chemie Japan Co., Ltd.] was added and dissolved. Next, when the polymeric dispersant was completely dissolved, 5.6 parts by mass of triethanolamine as a reducing agent was added to reduce and precipitate the silver into fine particles. At this point, the silver concentration was 10.8% by mass. Next, the reaction solution was desalted by ion exchange treatment and further concentrated to prepare a silver colloid solution. In the total volume of the silver colloid solution, the proportions of each component were 50% by mass of silver, 2% by mass of polymeric dispersant, and 48% by mass of water.

[0103] (Ink preparation) To 25 parts by mass of the above silver colloid solution, the following components were added in the proportions shown in Table 3, stirred and mixed, and then filtered using a 3 μm membrane filter to prepare an ink for forming a conductive layer.

[0104] Surfactants: Silicone-based surfactants Higher alcohol: Cetyl alcohol [Conol 1695, manufactured by Shin Nippon Rika Co., Ltd., C16: ≥99%] Water: Ultra pure water Lower alcohol: Ethanol [Number of carbon atoms: 2]

[0105] [Table 3]

[0106] The proportion of water in the total volume of the silver colloid solution (12 parts by mass) and ethanol was 45.0% by mass, and the proportion of silver fine particles in the total volume of ink was 12.5% ​​by mass.

[0107] <Ink 2> The ink was prepared in the same manner as Ink 1, except that the amount of water added during ink preparation was 74.60 parts by mass, and ethanol was not included.

[0108] The proportion of water in the total amount of water added to the silver colloid solution (12 parts by mass) and ethanol was 100.0% by mass, and the proportion of silver fine particles in the total amount of ink was 12.5% ​​by mass.

[0109] <Ink 3-7> The ink was prepared in the same manner as Ink 1, except that the amounts of water and ethanol added during ink preparation were the parts by mass shown in Table 4.

[0110] Table 4 shows the proportion of water (12 parts by mass) added to the silver colloid solution and the total amount of water in the ethanol solution. In all cases, the proportion of silver fine particles in the total amount of ink was 12.5% ​​by mass.

[0111] [Table 4]

[0112] <Ink 8> Ink was prepared in the same manner as Ink 1, except that the amount of water added during ink preparation was 32.30 parts by mass, the amount of ethanol was 42.50 parts by mass, and cetyl alcohol was not included.

[0113] The proportion of water in the total amount of water added to the silver colloid solution (12 parts by mass) and ethanol was 51.0% by mass, and the proportion of silver fine particles in the total amount of ink was 12.5% ​​by mass.

[0114] <Ink 9-11> The ink was prepared in the same manner as Ink 1, except that the amounts of water, ethanol, and cetyl alcohol added during ink preparation were the parts by mass shown in Table 5.

[0115] Table 5 shows the proportion of water (12 parts by mass) added to the silver colloid solution and the total amount of water in the ethanol solution. In all cases, the proportion of silver fine particles in the total amount of ink was 12.5% ​​by mass.

[0116] [Table 5]

[0117] Manufacturing of printing sets and conductive components. <Examples 1-21, Comparative Examples 1 and 2> The recording media of Examples i to xii described above, along with inks 1 to 11, were combined to form a printing set as shown in Tables 6 to 11. A conductive layer was then patterned on the printed surface of the recording media to produce a model of an IC tag as a conductive component. The following characteristics were then evaluated.

[0118] (Conductivity evaluation) On the printing surface of the recording media of Examples i to xii, a rectangular conductive layer with a width of 5 mm and a length of 5 cm was formed twice by inkjet printing using one of inks 1 to 11, at a resolution of 600 dpi.

[0119] After allowing the material to stand for 10 minutes immediately after printing, the resistance (Ω) between the two ends of the conductive layer was measured using a resistance meter [RM3545 manufactured by HIOKI E. CORPORATION] with a four-prong probe method, and the conductivity was evaluated according to the following criteria.

[0120] ◎: 50Ω or less. ○: Greater than 50Ω and 200Ω or less. △: Greater than 200Ω and 500Ω or less. ×: Greater than 500Ω.

[0121] (Drying properties evaluation) On the printing surface of the recording media of Examples i to xii, a rectangular conductive layer with a width of 5 mm and a length of 5 cm was patterned once by inkjet printing using one of inks 1 to 11 at a resolution of 600 dpi.

[0122] Then, after the conductive layer had been left to stand for a certain period of time immediately after printing, a piece of paper was placed on top, and a 10cm x 10cm, 700g metal plate was placed on top of it. The presence or absence of ink transfer (show-through) to the paper piece was observed. The drying properties of the ink were then evaluated according to the following criteria.

[0123] ○: No bleed-through occurred even after a standing time of 5 minutes. △: Bleed-through occurred after a standing time of 5 minutes, but not after 10 minutes. ×: Bleed-through occurred even after a standing time of 10 minutes.

[0124] (Intermittent printing performance evaluation) On the printable surface of the recording media of Examples i to xii, a rectangular conductive layer with a width of 5 mm and a length of 5 cm was patterned once by inkjet printing using one of inks 1 to 11 at a resolution of 600 dpi. Next, the inkjet printer was stopped for a certain period of time in the decapping state, and then the same conductive layer was patterned once again by inkjet printing under the same conditions on the printable surface of a separately prepared identical recording media. After printing was resumed, the state of the formed conductive layer was observed, and the intermittent printability of the ink was evaluated according to the following criteria.

[0125] ○: No chipping or damage was observed in the conductive layer even with a 10-minute stop. △: Chipping or damage was observed in the conductive layer with a 10-minute stop, but no chipping or damage was observed with a 5-minute stop. ×: Chipping or damage was observed in the conductive layer even with a 5-minute stop, and the chipping or damage was not resolved unless the stop time was reduced to 1 minute or less.

[0126] The results are shown in Tables 6 to 10. In the tables, PVAc in the hydrophilic resin column refers to polyvinyl acetal, and PVA refers to polyvinyl alcohol. Also, "Water (mass%)" indicates the percentage of water in the total amount of water added to the silver colloid solution and ethanol as a lower alcohol, as mentioned above.

[0127] [Table 6]

[0128] [Table 7]

[0129] [Table 8]

[0130] [Table 9]

[0131] [Table 10]

[0132] From the results of Examples 1-12 and Comparative Example 1 in Tables 1-10, it was found that the ink receiving layer of the recording medium needs to be a layer containing a hydrophilic resin, a filler, and a water-soluble sulfate. Furthermore, from the results of Examples 1, 4-6, it was found that polyvinyl acetal with an acetalization degree of 50 mol% or less is preferred as the hydrophilic resin.

[0133] From the results of Examples 1 to 3, it was found that sodium salts or magnesium salts are preferred as sulfates. From the results of Examples 1, 7 to 12, it was found that the proportion of sulfates is preferably 5 parts by mass or more, particularly 10 parts by mass or more, and 35 parts by mass or less, particularly 30 parts by mass or less, based on anhydrous basis, of 100 parts by mass of the total amount of solids forming the ink receiving layer.

[0134] From the results of Example 1 and Comparative Example 2, it was found that the ink to be combined with the above recording medium needs to contain metal fine particles treated with a dispersant, water, and a lower alcohol. Furthermore, from the results of Examples 1, 13-17, it was found that the proportion of water in the total amount of water and lower alcohol is preferably 20% by mass or more, particularly 30% by mass or more, and preferably 75% by mass or less, particularly 70% by mass or less. In addition, from the results of Examples 1, 18-21, it was found that the ink also preferably contains a higher alcohol with 12 or more carbon atoms, and that its proportion is preferably 0.10 parts by mass or more and 1.00 parts by mass or less in 100 parts by mass of the total amount of ink.

[0135] [Study on the impact on the thermal recording layer] Test Example 1 involved creating a recording medium identical to that used in Example 1, with an ink-receiving layer formed on one side of the substrate via a barrier layer. On the opposite side of this recording medium, a thermal recording layer combining a leuco dye and a developer was formed beforehand, prior to the formation of the ink-receiving layer. Using ink 1, ink 1 was used to create a pattern on the printed surface of the recording medium in Test Example 1 by inkjet printing, overlapping rectangular conductive layers with a width of 5 mm and a length of 5 cm twice at a resolution of 600 dpi. After being left to stand for 10 minutes immediately after printing, the material was evaluated in the same manner as described above. The conductivity was "◎" and the drying speed was "○". Furthermore, thermal recording was performed on the thermal recording layer without any problems.

[0136] On the other hand, when the barrier layer was omitted in Test Example 1 and evaluated similarly as Test Example 2, the conductivity was "◎" and the drying properties were "○". However, when thermal recording was performed on the thermal recording layer, the color development was faint and good recording could not be achieved.

[0137] Furthermore, when a conductive layer was patterned on the recording medium of Test Example 1 using ink 2 and evaluated similarly as Test Example 3, the conductivity was "◎" but the drying properties were "×". Therefore, after hot air drying, thermal recording was performed on the thermal recording layer, but the color development was faint and good recording could not be achieved.

[0138] From the above results, it was found that when the surface opposite to the surface on which the ink-receiving layer is formed is used as the thermal recording surface, interposing a barrier layer between the substrate and the ink-receiving layer can suppress the background coloring of the thermal recording layer or the occurrence of poor color development during thermal recording, even if alcohol is contained in the coating agent or ink for the ink-receiving layer. Furthermore, it was found that it is preferable to use an ink containing water and lower alcohol, and to form the conductive layer in an environment at room temperature without firing.

Claims

1. A recording medium including a printing surface for forming a conductive layer by inkjet printing an ink containing metal fine particles treated with a dispersant, water, and a lower alcohol, the recording medium comprising: a substrate; an ink-receiving layer that is formed on at least one surface of the substrate to constitute the printing surface, the ink-receiving layer containing a hydrophilic resin, a filler, and a sulfate capable of forming a hydrate, and that receives the ink; A recording medium comprising:

2. 2. The recording medium according to claim 1, wherein the sulfate contained in the ink receiving layer is at least one selected from the group consisting of sodium sulfate and aluminum sulfate.

3. 2. The recording medium according to claim 1, wherein the hydrophilic resin contained in the ink receiving layer is polyvinyl acetal.

4. 2. The recording medium according to claim 1, wherein the filler contained in the ink receiving layer is silica.

5. 2. The recording medium according to claim 1, wherein the ink receiving layer is formed on one side of the substrate via a barrier layer to form the printing surface, and the opposite side of the substrate is a thermal recording surface.

6. a recording medium according to any one of claims 1 to 5; an ink for forming the conductive layer by inkjet printing on the printing surface of the recording medium, the ink comprising metal particles treated with a dispersant, water, and a lower alcohol; Print set including:

7. The print set according to claim 6, wherein the lower alcohol is a lower alcohol having 1 to 3 carbon atoms, and the proportion of the water in the total amount of the water and the lower alcohol having 1 to 3 carbon atoms is 20% by mass or more and 75% by mass or less.

8. The print set of claim 6 , wherein the ink further comprises a higher alcohol having 12 or more carbon atoms.

9. A method for manufacturing a conductive member, comprising a step of inkjet printing an ink containing metal particles treated with a dispersant, water, and a lower alcohol onto the printing surface of the recording medium described in any one of claims 1 to 5 to form the conductive layer.

10. The method for producing a conductive member according to claim 9, wherein the lower alcohol is a lower alcohol having 1 to 3 carbon atoms, and the proportion of the water in the total amount of the water and the lower alcohol having 1 to 3 carbon atoms is 20 mass% or more and 75 mass% or less.

11. The method for producing a conductive member according to claim 9 , wherein the ink further contains a higher alcohol having 12 or more carbon atoms.

12. The method for manufacturing a conductive member according to claim 9 , wherein the conductive member is an IC tag including an IC chip, the conductive layer is an antenna for the IC chip, and the method further comprises a step of mounting the IC chip on the formed conductive layer.